Implementation of CHSE-based hygiene standards at Horison Rahaya Resort Hotel as a tourist accommodation provider based on Permenparekraf Number 13 of 2020 concerning Standards and Certification of Hygiene, Health, Safety, and Environmental Sustainability - Salsabila, Azka Alifa (Beleid, 2023)
Health and safety factors are important aspects in the tourism industry amid the Covid-19 pandemic. The tourism sector has begun to tighten the implementation of health protocols using the CHSE guidelines. CHSE is a program of the Ministry of Tourism and Creative Economy in the form of implementing health protocols based on Cleanliness, Health, Safety and Environment Sustainability. The application of this program is to certify business actors in the tourism industry. The aim of this research is to provide advice to tourism businesses to continue implementing CHSE supporting indicators well.Identification of the problem in this study, namely, How is the implementation of CHSE standards at Hotel Horison Rahaya Resort Lebak as a tourist accommodation providerbased on Permenparekraf Number 13 of 2020? And how is the implementation of CHSE standards at Hotel Horison Rahaya Resort Lebak as a tourist accommodation provider based on Permenparekraf Number 13 of 2020? The theory used is the theory of tourism management and supervision theory. This study uses an empirical juridical method. The specification of the research used is descriptive analytical research. This study uses primary data sources and secondary data. Data collection techniques in this study are using field research techniques, library research. Data analysis in this study used a qualitative descriptive approach. The result of this study is that Permenparekraf Number 13 of 2020 was not implemented. The conclusion of this study is that the Horison Rahaya Resort Hotel has passed the CHSE audit by the team from Sucofindo by fulfilling 70 CHSE assessment indicators, but there are 12 assessment points that are not met. Supervision by the Regional Government does not work in accordance with Article 20 of Permenparekraf Number 13 of 2020 because there is no coordination with the Certification Agency so that the form of direct supervision, namely monitoring and evaluation, is not carried out by the Regional Government or Sucofindo which has supervisory duties. Suggestions from this study are that the hotel should continue to improve services without reducing the aspects contained in the assessment indicators so that they continue to experience progress. The CHSE monitoring process should be periodically evaluated to ensure that the protocols implemented are truly effective.